Blood fatty acids analysis in captive false gharial (Tomistoma schlegelii) - Sarkawi, Nur Nabila (2016)
Fatty acid is an important physiological tool to further understand the animal‟s body mechanism. Any data obtained from the analysis might help in captive wildlife management and thus improving their quality of life especially for those species that are on the brink of extinction. Research on the fatty acid composition in false gharial is limited compared to other crocodilian species. Therefore, fatty acid study was done on five captive false gharials consisting of two males and three females. The fatty acid composition is then further investigated by taking into account their essential fatty acid composition in the diet. Blood sample was collected from lateral tail vein using 18G spinal needle for plasma fatty acid analysis and feed sample comprised of chicken and fish meat was also analysed. Then, identification and quantification of fatty acid composition was done by using gas chromatography following the procedure of total lipid extraction and fatty acids methyl esters (FAME) preparation. The plasma fatty acid result showed all of the false gharials have predominant increase in unsaturated fatty acids. Specifically, polyunsaturated fatty acids was the highest, followed by saturated fatty acids and monounsaturated fatty acids with 47.30%, 29.24% and 23.47% respectively. Based on feed fatty acid analysis, chicken and fish was known to be the dietary source of omega-6 polyunsaturated fatty acid. As there was lack of dietary source in omega-3 polyunsaturated fatty acid, eicosapentaenoic acid (EPA, C20:5 n-3) value in plasma was also found to be low. On the contrary, docosahexaenoic acid (DHA, C22:6 n-3) was significantly high compared to other species of crocodilian and in relation to the fatty acid values obtained from feed (chicken and fish). Thus, several possible contributing factors were pointed out regarding the high DHA content in the plasma. In conclusion, the fatty acid composition in false gharial is not solely affected by the diet, but it can also depend on how its body mechanism react to other sources from the environment.